Arabic Language Learning Methods : Innovations And Challenges In The Digital Era - Alim Mujahidin; Abdul Ghofur; Muhammad Nanang Qosim (al-Afkar, Journal For Islamic Studies, 2025)
Arabic language learning in the digital era faces various challenges that impact the quality of education. Key issues include the widespread use of Arabic 'Amiyah, which undermines fluency, unclear goals and objectives in Arabic language education at universities, and a misalignment between educational vision and the curriculum. Additionally, the lack of clear policies in Arabic language teaching and low student motivation further exacerbate the situation. However, digital transformation offers opportunities to address these challenges through innovative teaching methods. The use of digital tools, such as games, quizzes, and online discussion forums, can enhance student participation and motivation. A Higher Order Thinking Skills (HOTS) approach also encourages critical, analytical, and creative thinking. With HOTS, students are encouraged to solve complex problems, connect concepts, and apply knowledge to real-world situations. Therefore, the integration of digital technology in Arabic language education has the potential not only to overcome existing challenges but also to improve the quality of learning in the digital age, enabling students to achieve greater language proficiency.